Investigating foods and beverages sold and advertised in deprived urban neighbourhoods in Ghana and Kenya: a cross-sectional study - Green, M.A.; Aryeetey, R.N.O.; Coleman, N.; et al. (BMJ Open, 2020)
Objectives This study aimed to characterize the local foods and beverages sold and advertised in three deprived urban African neighborhoods. Design Cross-sectional observational study. We undertook an audit of all food outlets (outlet type and food sold) and food advertisements. Descriptive statistics were used to summarise exposures. Latent class analysis was used to explore the interactions between food advertisements, food outlet types, and food type availability. Setting Three deprived neighborhoods in African cities: Jamestown in Accra, Ho Dome in Ho (both Ghana) and Makadara in Nairobi (Kenya). The main outcome measures Types of foods and beverages sold and/or advertised. Results Jamestown (80.5%) and Makadara (70.9%) were dominated by informal vendors. There was a wide diversity of foods, with high availability of healthy (eg, staples, vegetables) and unhealthy foods (eg, processed/ fried foods, sugar-sweetened beverages). Almost half of all advertisements were for sugar-sweetened beverages (48.3%), with higher exposure to alcohol adverts compared with other items as well (28.5%). We identified five latent classes which demonstrated the clustering of healthier foods in informal outlets, and unhealthy foods in formal outlets. Conclusion Our study presents one of the most detailed geospatial exploration of the urban food environment in Africa. High exposure to sugar-sweetened beverages and alcohol both available and advertised represent changing urban food environments. The concentration of unhealthy foods and beverages in formal outlets and advertisements of unhealthy products may offer important policy opportunities for regulation and action.
Research Article
Keywords: foods and beverages; deprived urban neighbourhoods; Kenya